Analysis of Impact of Foreign Direct Investment on unemployment in Sub-saharan Africa. The case of Ghana. - Kissi Susana Asantewaa (2019)
Ghana like any other developing country, relies on external source of financial assistance for capital projects and budgetary support. This study aims at understanding the impact of foreign direct investment on unemployment in Sub-Saharan Africa, particularly in Ghana. Given the region’s low income and domestic savings level, and its limited ability to raise funds domestically, a great part of its finance for the future will have to come in the form of FDI. FDI continues to play a significant role in bridging the unemployment gap and support the governments quest to provide jobs for the people. As a result of this, this study examines the relationship between FDI and unemployment in Ghana for a period of 10 years from 2009 to 2018. The explanatory parameters used to explain unemployment include: education, population, GDP per capita and FDI. The results from multiple linear regression estimation shows that FDI alone is not a sufficient parameter for explaining unemployment. The estimation showed that FDI has no impact on unemployment based on the p-value which was found to be statically insignificant. Education and population results on the contrary were statistically significant and influence unemployment. The researcher believes the high incidence of unemployment among the youth and secondary school leavers in recent times requires intervention including support for start-up capital and entrepreneurial training in order to attract young school leavers to become creators instead of job seekers. The study also recommends that policies that promote investment should be put in place to encourage Ghanaians to reinvest in the country.